THE RARE CASE OF NON-METASTATIC PENILE CANCER IN UROLOGY SERVICE OF ALIABAD TEACHING HOSPITAL - M.H. Kamran (Interdisciplinary Approaches to Medicine, 2020)
Abstract. Penile cancer is a very rare cancer of urogenital system of males which occurs in one in every 100000 individuals annually. Senescence, poor personal hygiene, and existence of prepuce are the contributing risk factors. About 95% of the cases are of squamous cell carcinoma type. Metastasis to the nearby lymph nodes indicates poor prognosis. Hence, physical examination, especially palpation of the inguinal region is vital to diagnose the disease and predict the prognosis. The best treatment choice is surgery, and, in case of lymphatic metastasis to the inguinal region, dissection of the lymph nodes.An 80-year-old man, complaining about a painless ulcer in his penis, was hospitalized on July 14, 2019 in the urology service of Aliabad Teaching Hospital. The patient had been suffering from the ulcer for three years. The ulcer had been small in size for the first two years. It, then, had enlarged and caused urinary retention for one year. Thus, cystostomy had been performed. The ulcer was inspected red which was occupying the distal half of the penis. Moreover, the glans was completely destroyed. However, the inguinal lymph nodes were found normal in size in palpation. Biopsy indicated a squamous cell carci- noma. A partial penectomy was consequently carried out.This particular case implies that penile ulcers especially in the glans could be the primary sign of a penile cancer. Therefore, the patient had better be consulted regarding biopsy, pathological examina- tions and early diagnosis and treatment.